Assessment of NIR Pigments for Use in Low Temperature Solar Thermal Collectors - OLIVER PENNEY (2022)
This EngD Thesis investigated the addition of Near Infrared (NIR) absorbing pigments into pre-finished steel coatings intended for use on the Transpired Solar Collector (TSC). The aim of the research was to improve the temperature uplift (ΔT) of lighter coloured coatings for the TSC, without affecting the aesthetics of the coating, because NIR light is invisible to the human eye. A solar simulator was designed, built and calibrated to measure the ΔT of Hot Dip Galv (HDG) sample panels coated with NIR pigmented paints. Correlation of these ΔT results were then made with further analysis of the samples using the UV/Vis/NIR spectrometer, photographic records, and colour change measurements (ΔE). A model PVB coating was initially used to assess a range of commercially available, as well as novel single compound NIR absorbing pigments at a range of concentrations. The best four performing pigments were taken forward for inclusion in a polyurethane clear coat system. This work revealed that the method of processing the pigments into the paint had a large effect on coating performance, particularly for the nano powders. A single pigment, the Cesium Tungsten Oxide Nano Powder (Cs0.33WO3) was selected for the final stages of this research due to its combination of excellent NIR absorption and relatively low visual absorption and therefore ΔE. This was added to the clear coat and colour coat of two light coloured paints and produced promising results, especially for the darker of the two colours. The results of outdoor testing also helped to reveal where in the coating structure the pigment was most effective. Finally, using the UV/Vis/NIR data and TSR calculations a simple assessment on the overall impact of these additions was made. This concluded that savings of 250 kWh (52 kg of CO2) could be made annually for an average UK home over a non NIR pigmented coating.